Comparison of postoperative analgesic effectiveness of combined intraperitoneal instillation and periportal infiltration of bupivacaine with intraperitoneal instillation or periportal infiltration alone for laparoscopic cholecystectomy - Bhattarai, Prajjwal Raj; Bhattarai, Balkrishna; Sah, Birendra Prasad; Rahman, Tanvir R; Ghimire, Ashish; Adhikary, Shailesh (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: Visceral pain is the major component of pain after laparoscopic cholecystectomy. Periportal infiltration and peritoneal instillation of local anesthetics have been reported to be effective in various laparoscopic procedures. Aim of this study was to find out the analgesic effectiveness and duration of analgesia following combined intraperitoneal instillation and periportal infiltration of bupivacaine and to compare it with peritoneal instillation or periportal infiltration alone. Methods: A prospective, randomized, double blinded study was conducted in 90 adult patients undergoing elective laparoscopic cholecystectomy. The patients were randomized into three groups. Group 1 received intraperitoneal instillation of 20 ml of 0.5% bupivacaine. Group 2 received periportal infiltration of 10 ml of 0.25% bupivacaine. Group 3 received combination of both. After standard balanced anesthesia technique, patients were observed in postoperative period for pain and hemodynamic variables, that were recorded ½ hourly for 1 hour, then at 4, 8, 12 and 24 hours postoperatively. The time and doses for rescue analgesia, if given, were also recorded. Results: Combined peritoneal instillation and periportal infiltration provided a mean duration of analgesia of 6 hours. Peritoneal instillation alone provided analgesia for three hours while periportal infiltration alone provided analgesia for one hour. The combination group required one third (116.67 mg vs. 173.33 mg) less analgesic than periportal group and one fifth (116.67 mg vs. 148.33 mg) less than that of peritoneal group. No adverse effects were noted. Conclusion: Combined intraperitoneal instillation and periportal infiltration of bupivacaine reduced postoperative pain after laparoscopic cholecystectomy better than intraperitoneal instillation or periportal infiltration of bupivacaine alone. Journal of Society of Anesthesiologists 2014 1(2): 59-64